Synchrotron scanning reveals the deep evolutionary root of the mammalian brain: the surprisingly advanced endocast morphology of Lumkuia fuzzi (Cynodontia: Probainognathia) - Benoit, Julien (My University, 2023)
The mammalian brain is very distinctive for its large relative size, enlarged olfactory bulbs, and layered isocortex. These defining traits likely evolved in the non-mammalian probainognathian cynodonts, although the timing and exact phylogenetic sequence in which these characters evolved is not well understood. The endocast of the brain cavity provides a unique window into the evolution of the central nervous system of extinct species. The endocast of the basal-most probainognathian, Lumkuia fuzzi, is here described for the first time. Its olfactory bulbs are relatively large despite that its encephalization quotient is lower than in Mammaliaformes. This contradicts the consensually established hypothesis that encephalization and olfaction evolved in concert. Moreover, the data presented here do not indisputably distinguish between the encephalization quotients of Mesozoic mammals, non-mammalian mammaliaforms, and non-mammaliaform cynodonts, which suggests that brain enlargement was gradual in this lineage. Lumkuia also possesses marked cerebral hemispheres, which is traditionally interpreted as the sign of the presence of an isocortex and hair. The enlarged olfactory bulbs and cerebral hemisphere in Lumkuia strongly support that the defining features of the mammalian brain began evolving in the last common ancestor of the Probainognathia clade, as early as the early Anisian.